Bubble Map’ Untuk Pembelajaran ‘Adjective’ Bagi Siswa Sekolah Dasar Sebagai Pengenalan Lokasi Pariwisata Untuk Pengunjung Kawasan Teluk Tomini - Wardatul Jannah Husain , Sabrina; El Walidayni Kau, Magvirah (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2024)
This service activity aims to improve children's English vocabulary, particularly adjectives, which will be useful later when describing tourist attractions around them. This may benefit children in promoting tourist destinations to visitors from other countries. Children will be taught to use simple English adjectives using the "Bubble Map" method. This activity targeted a total of 20 pupils from State Elementary School No. 2 Kabila Bone District, Bone Bolango Regency. This service activity will be limited to a single 90-minute meeting. It is intended that the "Bubble Map" method will help children improve their vocabulary of adjectives, particularly ones that may be used to promote tourist destinations around them. The bubble map method for teaching vocabulary to children has proven to be effective because it uses visualization to help children remember the relationships between words and can significantly improve vocabulary retention and understanding when compared to traditional teaching methods